Synthesis, In Vitro Antimicrobial Activity, and Molecular Docking Study of Novel Benzylidene Ketamine Analogues as Potential Elongation Factor Tu Inhibitors - Abraham Sisein Eboh; Azibanasamesa D. C. Owaba; Darlington D. Eboh; Okpenkuwo G. Francis; Charis Tiemo; Laura O. Edward (Candela Edutech Indonesia, 2026)
The rapid emergence of antimicrobial resistance (AMR) has become a critical global health challenge, leading to prolonged hospitalization, increased healthcare costs, and higher mortality rates. The declining efficacy of conventional antibiotics highlights the urgent need for novel antimicrobial agents with alternative mechanisms of action. This study evaluated the antimicrobial activity of newly synthesized benzylidene ketamine derivatives and explored their potential interactions with bacterial elongation factor Tu (EF-Tu), an essential protein involved in bacterial protein synthesis. Antibacterial and antifungal activities of ketamine and its derivatives (D11-D15) were determined using the broth microdilution method at concentrations ranging from 1 to 512 μg/mL. Ciprofloxacin and fluconazole served as reference antibacterial and antifungal agents, respectively. Molecular docking against EF-Tu (PDB ID: 1DG1) was performed using AutoDock Vina to predict ligand–protein binding affinity. Among the tested compounds, D14 and D15 exhibited the strongest antibacterial activities, with minimum inhibitory concentrations (MICs) of 32 μg/mL against Bacillus subtilis and 64 μg/mL against Staphylococcus aureus, respectively, whereas ketamine showed no detectable antibacterial activity. None of the synthesized compounds inhibited the growth of Candida albicans, while fluconazole displayed an MIC of 1 μg/mL. Docking analysis indicated favorable binding interactions between the active derivatives and the EF-Tu binding site. These findings suggest that benzylidene modification of ketamine enhances antibacterial activity and identifies D14 and D15 as promising lead compounds for the development of EF-Tu-targeted antibacterial agents.